Neutral pH Fenton and photo-Fenton activity of Mo-doped iron-pyrite particles - Yadav M.; Kumar U.; Kumar De A.; Sinha I. (My University, 2025)
Low H2O2 utilization efficiency for hydroxyl radical generation, acidic pH, and recyclability are critical limitations of heterogeneous Fenton and photo-Fenton catalysts. The present research shows that the optimum Mo doping of FeS2 particles can largely alleviate these catalysis constraints. A solvothermal protocol was followed to prepare polyvinyl pyrrolidone (PVP) stabilized FeS2 and Mo-doped FeS2 particles. XRD observations showed that Mo doping increases the lattice parameters of FeS2. The band gap of the Mo-doped FeS2 particles decreased to 1.58 eV from the 2.24 eV value exhibited by pure FeS2 particles. Structural and electronic structure DFT calculations support these results. The Fenton and photo-Fenton p-nitrophenol (PNP) degradation at neutral pH on PVP-stabilized Mo-doped FeS2 and FeS2 particles were examined. The photo-Fenton results were substantially better than under Fenton conditions. The best PNP degradation photo-Fenton turnover frequency (TOF) recorded was 254.50 μmol g−1 min−1 on the PVP stabilized 4% Mo-doped FeS2 sample. The Mo-doped FeS2 catalysts were stable under photo-Fenton recycling, and the H2O2 (1.66 mM) required for these reactions was significantly lower than most reports (30-6000 mM). Given the economic importance of the latter in Fenton/photo-Fenton reactions, H2O2 normalized turnover frequency (13.85 and 153.31 mg−1 min−1 L for Fenton and photo-Fenton) values were used to evaluate catalytic activities. © 2024 The Royal Society of Chemistry.